Control of depletion layer width via amount of AuNPs for sensor response enhancement in ZnO nanostructure sensor - Wongrat E. (2014)
The ethanol sensing characteristics in ZnO nanostructure sensors with Au coating by sputtering technique were investigated. The enhancement of sensor response due to gold nanoparticles (AuNPs) on ZnO nanostructure sensors has been observed and explained by considering the catalytic effect on ethanol adsorption reaction and oxygen adsorption reaction. Consequently, the sensor response formula has been developed based on the adsorption reactions. In addition, the dependence of gold amount on gas sensor response was systematically investigated. It was found that under the ethanol concentration of 1000 ppm, the sensor response increased as the sputtering time increased, exhibited maximum value of 478 at sputtering time of 60 s, and then, decreased at longer sputtering time. Based on the results, the developed formula can describe the dependence of gold amount on sensor response in terms of the depletion layer width. As a result, the sensor response can be designed by controlling the depletion layer width via the amount of gold nanoparticles (AuNPs), which can be simply performed by varying sputtering time. These results can be further explored for their an implication in e-nose applications. © 2012 Elsevier B.V. All rights reserved.